Proteomic profiling reveals an association between ALDH and oxidative phosphorylation and DNA damage repair pathways in human colon adenocarcinoma stem cells - Wang, Yewei; Chen, Ying; Garcia-Milian, Rolando; Golla, Jaya Prakash; Charkoftaki, Georgia; Lam, TuKiet T.; Thompson, David C.; Vasiliou, Vasilis (Chemico-biological interactions, 2022)
Several members of the aldehyde dehydrogenase (ALDH) family, especially ALDH1 isoenzymes, have been identified as biomarkers of cancer stem cells (CSCs), a small subpopulation of oncogenic cells with self-renewal and multipotency capability. Consistent with this contention, cell populations with high ALDH enzymatic activity exhibit greater carcinogenic potential. It has been reported that ALDH1, especially ALDH1A1, serves as a valuable biomarker for colon CSCs. However, the functional roles of ALDHs in CSCs and solid tumors of the colon tissue is not fully understood. The aim of the present study was to identify molecular signature associated with high ALDH activity in human colorectal adenocarcinoma (COLO320DM) cells by proteomics profiling. Aldefluor™ assay was performed to sort COLO320DM cells exhibiting high (ALDHhigh) and low (ALDHlow) ALDH activity. Label-free quantitative proteomics analyses were conducted on these two cell populations. Proteomics profiling revealed a total of 229 differentially expressed proteins (DEPs) in ALDHhigh relative to ALDHlow cells, of which 182 were down-regulated and 47 were up-regulated. In agreement with previous studies, ALDH1A1 appeared to be the principal ALDH isozyme contributing to the Aldefluor™ assay activity in COLO320DM cells. Ingenuity pathway analysis of the proteomic datasets indicated that DEPs were associated with mitochondrial dysfunction, sirtuin signaling, oxidative phosphorylation and nucleotide excision repair. Our proteomics study predicts that high ALDH1A1 activity may be involved in these cellular pathways to promote a metabolic switch and cellular survival of CSCs. •ALDH enzymatic activity in ALDHhigh COLO320DM cells is mainly due to ALDH1A1.•There were 229 differentially expressed proteins (DEPs) in ALDHhigh cells.•DEP enrichment analyses predicted associations between ALDH activity and 3 pathways.•Inhibited pathways included oxidative phosphorylation and nucleotide excision repair.•Activated pathways included sirtuin signaling.